2014
DOI: 10.1111/echo.12817
|View full text |Cite
|
Sign up to set email alerts
|

Early Improvement in Left Atrial Remodeling and Function after Mitral Valve Repair or Replacement in Organic Symptomatic Mitral Regurgitation Assessed by Three‐Dimensional Echocardiography

Abstract: Early LA reverse remodeling and functional improvement occur after successful surgery of symptomatic organic MR regardless of surgical technique. Diastolic blood pressure and transmitral mean gradient augmentation are variables negatively related to Vol-max reduction. Besides, e' is positively correlated with both Vol-max reduction and AAEF increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
(41 reference statements)
1
8
0
1
Order By: Relevance
“…Similarly, SR patients showed a reduction in atrial function when compared to normal values of healthy controls (transmitral A wave velocity 54.7 ± 20.0 cm/s versus 80 ± 20 cm/s [19]; TDI lateral a’ wave 4.6 ± 1.7 cm/s, septal a’ wave 6.0 ± 2.0 cm/s, averaged a’ wave 5.3 ± 1.5 cm/s versus values >7.3 cm/s [17]; LA ejection fraction by areas 17.2 ± 5.0% versus 45% [15]; total emptying fraction by volumes 25.1 ± 7.3% versus normal values ranging from 45% to 65 ± 9% [18,20,21]; active and passive emptying fractions by volumes 11.4 ± 5.4% and 15.5 ± 6.3% versus 46.6 ± 11.7% and 44.3 ± 12.1% [22], respectively; global strain 9.8 ± 3.8% versus 22.9 ± 11.7% [23]). All these parameters, however, were less severely depressed compared to patients with arrhythmia relapses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, SR patients showed a reduction in atrial function when compared to normal values of healthy controls (transmitral A wave velocity 54.7 ± 20.0 cm/s versus 80 ± 20 cm/s [19]; TDI lateral a’ wave 4.6 ± 1.7 cm/s, septal a’ wave 6.0 ± 2.0 cm/s, averaged a’ wave 5.3 ± 1.5 cm/s versus values >7.3 cm/s [17]; LA ejection fraction by areas 17.2 ± 5.0% versus 45% [15]; total emptying fraction by volumes 25.1 ± 7.3% versus normal values ranging from 45% to 65 ± 9% [18,20,21]; active and passive emptying fractions by volumes 11.4 ± 5.4% and 15.5 ± 6.3% versus 46.6 ± 11.7% and 44.3 ± 12.1% [22], respectively; global strain 9.8 ± 3.8% versus 22.9 ± 11.7% [23]). All these parameters, however, were less severely depressed compared to patients with arrhythmia relapses.…”
Section: Resultsmentioning
confidence: 99%
“…226 Correction of MR reverses many features of atrial remodelling and corrects functional abnormalities. Early LA reverse remodelling (45% reduction of mean LA maximal volume) and increased active atrial emptying was found in the early (30 day) postoperative period in 43 patients undergoing mitral valve surgery (successful repair or replacement) for chronic organic MR 227 and a similar improvement at 6 months was reported by Dardas et al 228 Histologically, EHRAS Class III is the most prominent finding in MVD, although the histological appearance of the tissue may vary substantially over time and interindividually and, therefore, all EHRAS classes may be found in the tissue (see Figure 1; Table 2). …”
Section: Atrial Cardiomyopathy Due To Valvular Heart Diseasementioning
confidence: 99%
“…Early LA reverse remodelling (45% reduction of mean LA maximal volume) and increased active atrial emptying was found in the early (30 day) postoperative period in 43 patients undergoing mitral valve surgery (successful repair or replacement) for chronic organic MR 227 and a similar improvement at 6 months was reported by Dardas et al 228 Histologically, EHRAS Class III is the most prominent finding in MVD, although the histological appearance of the tissue may vary substantially over time and interindividually and, therefore, all EHRAS classes may be found in the tissue (see Figure 1; Table 2). …”
Section: Pathology Of Atrial Cardiomyopathiesmentioning
confidence: 99%